2004
DOI: 10.1016/s1525-2167(03)00050-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of left atrial size by freehand scanning three-dimensional echocardiography and two-dimensional echocardiography

Abstract: The 2D LA volumes provide a more accurate measure of the true size of the LA and are more sensitive to changes in LA size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
5
15
0
Order By: Relevance
“…It has been proposed that the LA enlarges asymmetrically; hence, LA volume, an index that encompasses multiplaner measurements, may be a more accurate and sensitive measure of LA size. 3,7,8 In the present study, the mean LA volume index for normal Japanese subjects using biplane Simpson's disc method was 22±4 ml/m 2 . Previously, different methods of LA volume measurement have been used: the biplane or single-plane area-length method, the biplane or single-plane Simpson's disc method, and the prolate-ellipsoid method.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…It has been proposed that the LA enlarges asymmetrically; hence, LA volume, an index that encompasses multiplaner measurements, may be a more accurate and sensitive measure of LA size. 3,7,8 In the present study, the mean LA volume index for normal Japanese subjects using biplane Simpson's disc method was 22±4 ml/m 2 . Previously, different methods of LA volume measurement have been used: the biplane or single-plane area-length method, the biplane or single-plane Simpson's disc method, and the prolate-ellipsoid method.…”
Section: Discussionsupporting
confidence: 43%
“…Two-dimensional (D) echocardiography-derived LA volume has been shown to provide a more accurate assessment of LA size than the M-mode LA dimension. [3][4][5][6][7][8] Recent studies demonstrated that the LA volume was more strongly associated with the future development of atrial fibrillation than LA dimension. 9,10 The LA volume was also strongly associated with the prognosis of patients with acute myocardial infarction 11 and dilated cardiomyopathy.…”
mentioning
confidence: 99%
“…Thus, the intrinsic ability of 3D imaging to directly measure right ventricular volumes without the need for geometrical modeling has resulted in significant improvements in accuracy and reproducibility compared with previously used 2D techniques [12,34,35••]. Similar results confirming improved accuracy and reproducibility of 3D's approach were reported by investigators who compared 2D and 3D echocardiographic measurements of left and right atrial volumes against an independent gold standard [36,37]. These findings may have important clinical implications for diagnosing and managing patients with congenital heart disease.…”
Section: Volumetric Analysis Of Other Cardiac Chamberssupporting
confidence: 52%
“…29,30 An advantage of 3D speckle-tracking is that it provides more spatial information on the entire cardiac chambers and more accurate measures of the LA cavity. 25, 26 Mochizuki et al showed that LA strain and dyssynchrony assessed by 3D speckle-tracking were feasible, reproducible, and beneficial compared with those by 2D speckle-tracking for identifying patients with PAF. 23 In addition to the studies described above, a previous study using 2D speckle-tracking demonstrated the improved mechanical properties of the left atrium by the recovery of LA mechanical synchrony (i.e., the reduction of dispersed atrial regional deformation as reflected by the decrease in TP-SD 24 ), so we further assessed LA functional conditions by not only LA strain but also TP-SD using 3D echocardiography.…”
Section: Assessment Of La Functionmentioning
confidence: 99%
“…In the present study, we assessed geometric and functional recovery, including LA dyssynchrony, of the left atrium in patients who underwent PVI for paroxysmal AF (PAF), using 3D strain speckle-tracking echocardiography. 26,27 …”
mentioning
confidence: 99%